ANALISIS MOTIVASI BELAJAR SISWA DALAM PELAJARAN BIOLOGI KELAS X DI SMK SWASTA AMAL MAS 1 LAHUSA JURUSAN ASISTEN KEPERAWATAN - Ferniwati Amazihono; Murnihati Sarumaha (Universitas Nias Raya, 2024)
This research aims to determine students' learning motivation, namely producing descriptive data in the form of written and verbal words from the people and behavior observed. The research method used is a qualitative research method with a descriptive method which aims to describe phenomena or symptoms that occur around and that can be seen. The data collection techniques used are observation, interviews and documents or archives. The subjects in this research were 20 students of the Amal-Mas 1 Lahusa Private Vocational School, majoring in Nursing Assistant. The research results show that student learning motivation has a very important role in the teaching and learning process for both teachers and students. So it can be concluded that learning motivation in learning shows the level at which students there have very good motivation. Learning motivation can influence student learning outcomes in biology subjects. Researcher suggestions (1) teachers should be able to understand the factors that can influence the results of student learning motivation. (2) Future researchers should carry out this research with a wider scope.